Estudio técnico para el desarrollo de una tienda online utilizando la metodología UML para compra y venta de productos en la piladora “bendición de dios” ubicada en el Recinto Rincón Grande-Herederos Rodríguez de la Parroquia Junquillal. - Vera Herrera, Edgar Arturo (2023)
Nowadays the traditional commerce has been revolutionized through online stories, allowing the business to grow efficiently, since they have advantages such as a wide geographic scope, the possibility of getting new potential customers, and keeping the customers information detailed and organized within a secure system. Through this research work, it has been evidenced that the owner of the milling “Bendición de Dios” does not have a system that helps record the information of his consumers, products, sales and purchases in an orderly and safe way. The aim is to carry out a technical study to develop an online store using the methodology of the Unified Modeling Language (UML) for the purchase and sale of products in the milling “Bendición de Dios” which is located in el recinto Rincón Grande-Herederos Rodríguez of the parroquia Junquillal. This case study was developed by means of the descriptive research method that allowed the data collection through an interview with the owner, a survey of the customers of milling in order to know their opinion with regard to developing an online shop for the business and likewise get the various sources of information as a reference. The technical, economic and operational evaluation were applied to determine that the project is feasible, also the presentation of UML diagrams, the use case specifications which facilitates the analysis and operation of the software. Lastly, it is expected that when implementing an online store for the purchase and sale of products, it will have a favorable acceptance by current customers, for as most agree to use it and it could acquire new potential customers, thus generating better income for the owner.